Novel Chemical Scaffolds to Inhibit the Neutral Amino Acid Transporter B0AT1 (SLC6A19), a Potential Target to Treat Metabolic Diseases - Yadav, Aditya; Shah, Nishank; Tiwari, Praveen Kumar; Javed, Kiran; Cheng, Qi; Aidhen, Indrapal Singh; Bröer, Stefan (Frontiers in Pharmacology, 2020)
Lack of B0AT1 (SLC6A19) partially protects mice against the onset of non-alcoholic steatohepatitis (NASH). To achieve a similar outcome through pharmacological treatment, we improved previously identified inhibitors of B0AT1 by medicinal chemistry and identified second generation inhibitors by high through-put screening. Modified diarylmethine compounds inhibited B0AT1 with IC50 values ranging from 8–90 μM. A second generation of inhibitors was derived from high-throughput screening and showed higher affinity (IC50 of 1–15 μM) and strong selectivity against amino acid transporters with similar substrate specificity, such as ASCT2 (SLC1A5) and LAT1 (SLC7A5). All compounds were unrelated to B0AT1 substrates, but were likely to bind in the vicinity of the substrate binding site.